2021
DOI: 10.3389/fvets.2021.688915
|View full text |Cite
|
Sign up to set email alerts
|

Selenium and Natural Zeolite Clinoptilolite Supplementation Increases Antioxidative Status and Immune Response in Growing Pigs

Abstract: Selenium (Se), an essential trace element for human and animal health, is covalently incorporated into amino acids, acts as a cofactor for antioxidant enzymes, and is involved in the maintenance of the immune system. The main goal of this investigation was to show the effect of Se supplementation, at levels slightly higher than the recommended values, combined with natural zeolite clinoptilolite on Se deposition in tissues (muscle and liver) and on the immune and antioxidative status of supplemented growing pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 49 publications
0
1
1
Order By: Relevance
“…However, the beneficial effect of zeolite was not observed under normal conditions [ [34] , [35] , [36] ], implying that zeolite was not a factor contributing to the improved growth performance or metabolic health in offspring induced by maternal MA consumption. Furthermore, dietary supplementation of zeolite had no effect on the BW of growing and finishing pigs [ 37 , 38 ], which was also inconsistent with the increased BW and litter weight of sucking piglets in this study. Therefore, the observed changes were attributed to MA in this study.…”
Section: Discussioncontrasting
confidence: 66%
“…However, the beneficial effect of zeolite was not observed under normal conditions [ [34] , [35] , [36] ], implying that zeolite was not a factor contributing to the improved growth performance or metabolic health in offspring induced by maternal MA consumption. Furthermore, dietary supplementation of zeolite had no effect on the BW of growing and finishing pigs [ 37 , 38 ], which was also inconsistent with the increased BW and litter weight of sucking piglets in this study. Therefore, the observed changes were attributed to MA in this study.…”
Section: Discussioncontrasting
confidence: 66%
“…For humans, meat products are the main source of dietary Se ( 47 ). The level of Se deposition in the muscle is considered an important indicator of Se levels in animals, and it is also suitable to indicate the adequacy of Se intake by humans ( 48 ). In this study, the content of Se in LD and TB of sheep fed on the Se deficiency diet was found significantly lower by 53.9 and 48.2%, respectively, than in LCG group, and not detected in BF.…”
Section: Discussionmentioning
confidence: 99%